PRRI dalam Bingkai Nasionalisme: Jejak Reuni Divisi Banteng dan Tuntutan Otonomi - M Budiman; Muhammad Junaldi Jufri (YASIN, 2026)
This article is motivated by the dominance of historiographical narratives that interpret the Pemerintahan Revolusioner Republik Indonesia (PRRI, Revolutionary Government of the Republic of Indonesia) solely as a separatist rebellion, without taking into account the context of center–region inequality and the dynamics of regional nationalism in the post-independence period. The study aims to analyze the role of the Reuni Divisi Banteng (Banteng Division Reunion) in the formation of the Dewan Banteng (Banteng Council) as the embryo of PRRI in West Sumatra and to explain the political, social, and ideological motives underlying it. Using a historical method with a sociological–critical approach and library research, the study follows the stages of heuristics, source criticism, interpretation, and historiography, with its analysis supported by grievance theory and a center–region inequality framework. The findings show that the establishment of the Dewan Banteng was rooted in the structural marginalization of former Banteng Division fighters and development disparities concentrated in Java. PRRI emerged as an articulation of collective discontent over the neglect of demands for regional autonomy and equitable development, while also gaining broad support from civil society and nationalist leaders. The study argues that PRRI was an expression of regional nationalism with a corrective character toward the centralization of power, rather than an attempt to secede from the Unitary State of the Republic of Indonesia. The conclusion challenges the labeling of PRRI merely as a rebellion and underscores the need to reassess Indonesia’s political history narrative. The findings imply the importance of historiographical revision and the strengthening of decentralization as a form of justice, recognition of regional contributions, and consolidation of post-independence national integration.